2020
DOI: 10.1080/20445911.2020.1776718
|View full text |Cite
|
Sign up to set email alerts
|

The cheerleader effect is robust to experimental manipulations of presentation time

Abstract: Pre-print Version 1 (October 2019): *This manuscript is undergoing peer-review and will be updated periodically* Total Word Count: 3850 approx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 38 publications
0
18
2
Order By: Relevance
“…Therefore, we recruited 100 participants in total for Experiment 2, so that 50 participants would complete each judgement condition. This sample size exceeds that of the vast majority of comparable cheerleader effect studies, which have typically recruited between 18-39 participants even for within-participants designs (Carragher et al, 2019(Carragher et al, , 2020Hsieh et al, 2020;Walker & Vul, 2014;Ying et al, 2019). Nonetheless, the results of each experiment in isolation should be accepted tentatively until they can be replicated with larger sample sizes (see General Discussion).…”
Section: Sample Sizementioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, we recruited 100 participants in total for Experiment 2, so that 50 participants would complete each judgement condition. This sample size exceeds that of the vast majority of comparable cheerleader effect studies, which have typically recruited between 18-39 participants even for within-participants designs (Carragher et al, 2019(Carragher et al, , 2020Hsieh et al, 2020;Walker & Vul, 2014;Ying et al, 2019). Nonetheless, the results of each experiment in isolation should be accepted tentatively until they can be replicated with larger sample sizes (see General Discussion).…”
Section: Sample Sizementioning
confidence: 97%
“…One sample t-tests are used to determine whether the change in judgement is statistically significant (Walker & Vul, 2014). Using this analytic approach, Carragher et al, (2020) have previously shown that the cheerleader effect occurs with a medium effect size (d = 0.50-0.70). An a priori power analysis indicated that 32 participants were required to achieve 90% power to detect an effect of d = 0.60 in a two-tailed one sample ttest with a conventional alpha of α = .05 (G*Power; Faul, Erdfelder, Lang, & Buchner, 2007).…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Given the importance of attractiveness and the broad agreement on the facial traits that are perceived as attractive (Langlois et al, 2000), it is perhaps surprising that perceptions of facial attractiveness are not necessarily stable and can be influenced by the presence of other surrounding faces (Carragher et al, 2019(Carragher et al, , 2020Carragher, Lawrence, et al, 2018;Geiselman et al, 1984;van Osch et al, 2015;Walker & Vul, 2014;Ying et al, 2019). One such finding, dubbed the "cheerleader effect" (Walker & Vul, 2014; or "friend effect," Ying et al, 2019), refers to the observation that faces are rated as more attractive when seen in a group of other faces compared with when seen in isolation (Carragher et al, 2019;Carragher, Lawrence, et al, 2018;Walker & Vul, 2014).…”
Section: Introductionmentioning
confidence: 99%